Critical characteristics of an airlift pump for dredging - Hu, Dong; Guo, Jingzhi; Deng, Ling; Yang, Fengling (Frontiers in Earth Science, 2022)
There are many factors that affect an airlift pump for dredging. In actual applications, if these factors cannot be fully considered, the performance of the airlift pump will be reduced. In view of this, based on the critical model of the water–solid two-phase flow and the gas holding model, a critical model of the gas–water–solid three-phase flow is proposed. The research results show that, compared with the two-phase flow, the critical water flow rate for lifting solids in the three-phase flow is always smaller. Therefore, it is necessary to consider the static chip retention force so that the critical model in the two-phase flow can be modified. It shows that the static chip retention effect is opposite to the “start” of the particle. Not only that, but also discussed are the critical conditions of solid particles or vertical lifting water from a practical point of view. The results show that solid particles will not affect the critical air flow rate of pumping water. However, the size and location of the solid particles affect the critical air flow rate.